Pericoronary adipose tissue density is associated with clinical disease activity in Takayasu arteritis and coronary arterial inflammation measured by 68Ga-DOTATATE PET in atherosclerosis. (25th November 2020) - Wall, C; Huang, Y; Uy, C; Le, E; Tombetti, E; Gopalan, D; Manavaki, R; Dweck, M; Ariff, B; Bennett, M; Slomka, P; Dey, D; et al.
Abstract: Background: Coronary artery disease (CAD) is an under-recognized complication of intense arterial inflammation in Takayasu arteritis (TAK). While pericoronary adipose tissue (PCAT) density is associated with arterial inflammation in CAD patients, this relationship has not previously been studied in TAK patients, nor directly compared with coronary arterial inflammation measured by 68Ga-DOTATATE positron emission tomography (PET). Purpose: To compare PCAT density with clinical, biochemical and molecular imaging markers of inflammation in TAK and CAD patients. Methods: PCAT density was quantified from computed tomography coronary angiography (CTCA) around each of the 17 coronary segments in patients with: (1) TAK and CAD, (2) atherosclerotic CAD, and (3) age and gender-matched healthy controls, using semi-automated software (Autoplaque). In TAK patients, PCAT density was compared to the Indian Takayasu Clinical Activity Score (ITAS) and high-sensitivity C-reactive protein (CRP). In CAD patients, PCAT density was compared to local arterial inflammation measured by coronary motion-frozen 68Ga-DOTATATE PET using image registration software (FusionQuant), and systemic (aortic) inflammation using 18F-fluorodeoxyglucose (FDG) PET. Data was acquired either during routine clinical care or prior research that established 68Ga-DOTATATE as an experimental marker of arterial inflammation that binds macrophage somatostatin receptor-2 in atherosclerotic plaques (NCT02021188). Results: 60 patients were included (TAK, n=20; CAD, n=20; healthy, n=20). Non-calcified plaque burden (TAK: 95.2%; CAD: 90.4%, p<0.0001) and CRP (TAK: 25.2 ±SD 16.1 mg/L; CAD: 2.5 ±SD 1.7 mg/L, p=0.04) were greater in TAK than CAD patients. PCAT density varied significantly among the three groups (median [IQR] TAK: −72.9 [−81.2 to -66.1] Hounsfield unit [HU]; CAD: −79.9 [−88.0 to −72.2]; healthy: −83.8 [−90.1 to −75.8] HU, p<0.0001). Figure: box-plot showing the distribution of PCAT values by group, with corresponding representative multiplanar reconstructed and cross-sectional CTCA images with surrounding PCAT density displayed by color table in left anterior descending arteries. PCAT density was significantly associated with ITAS (r=0.61, p=0.004) and CRP (r=0.43, p=0.03) in TAK patients, and coronary 68Ga-DOTATATE maximum tissue-to-blood ratio (r=0.31, p<0.001) in CAD patients. PCAT density was not associated with aortic 18F-FDG uptake in CAD patients, nor subcutaneous (pre-sternal) adipose tissue density in either disease group. No significant patient-level confounders were identified using linear mixed-effects regression modelling. Conclusion: PCAT density measured by CTCA is greater in TAK than CAD patients, and is associated with clinical and biochemical markers of disease activity in TAK, and coronary arterial inflammation measured by 68Ga-DOTATATE PET in CAD. PCAT could be a useful, easy to measure marker of coronary inflammation and disease activity in both TAK and CAD. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Wellcome Trust